Ovarian haemangioma in sows - Sheikh Omar, Abdul Rahman; M. Jaafar, (BMJ Publishing Group, 1985)
OVARIAN haemangioma in the sow was reported in the USA in 1967 and was considered to be rare (Nelson and others 1967) while some of the haemangiomas reportedly observed in sows were possibly misdiagnoses of vascular hamartomas (Jubb and Kennedy 1970). Scrotal haemangiomas of boars are, however, more frequently observed, as was reviewed by Wells and Morgan (1980), and its occurrence in Malaysia and Singapore has also been reported (Lee 1957, Wells and Morgan 1980).